Austenite grain growth and grain size distribution in isothermal heat-treatment of 300M steel. (2017) - Chen, R.C.; Hong, C.; Li, J.J.; Zheng, Z.Z.; Li, P.C.
Abstract: In order to investigate the austenite grain growth behavior in isothermal heat-treatment of 300M steel, experiments under different temperatures are conducted. The influences of time, temperature and initial grain size on both normal and abnormal growth of grains in heat-treatment of 300M steel are analyzed. Grain size distribution are modeled using a model which is a combination of the Sellars model and the Anelli model. Results show the model is capable of calculate grain size distribution as well as average grain size evolution with high precision. The mechanisms of austenite grain growth are observed by a confocal laser scanning microscope (VL2000DX) integrated with heating system (SVF17SP) in an in-situ heating experiment. Results indicate that the grain boundary migration is the main mechanism for austenite grain growth of 300M steel.